PENGGUNAAN BERBAGAI PLASMA NUTFAH KELAPA SAWIT KOLEKSI PPKS RIAU TERHADAP POPULASI SERANGGA PENYERBUK KELAPA SAWIT - Amnesty Situmeang Situmeang (Jurnal Pertanian Tropik, 2017)
This research was to study the use of various oil palm germplasm collection of Indonesian Oil PalmResearch Institute (IOPRI) Riau on a population of insect pollinators (Elaeidobius kamerunicus Faust.)in Riau Province Kalianta Gardens. The research was conducted from May until July 2016 bya purposive sampling method. The results showed that E. kamerunicus total population of 9,123head/0.5ha with E. kamerunicus male sex ratio of 3,160 head/0.5ha and females amounted to 5,963heads/0.5ha in male flowers and a total population of 433 head/0.5ha with a ratio E. kamerunicusmale genitals of 182 head/0.5ha and females of 251 head/0.5ha in the female flowers. The populationof E. kamerunicus on more male flowers than the female flowers. Germplasm highest in V3 (AccessionWild Angola) on the male flowers and V1 (Elaeis guineensis) in the female flowers, while the lowestgermplasm on male and female flowers are V7 (Elaeis oleifera).